2013
DOI: 10.3892/or.2013.2657
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of membrane progesterone receptor α to the induction of progesterone-mediated apoptosis associated with mitochondrial membrane disruption and caspase cascade activation in Jurkat cell lines

Abstract: In the present study, we investigated the effects of progesterone (Pg) on the growth of A3 and its caspase-8-deficient mutant cell line, I9.2, both of which are subclones of a T-cell-derived leukemic Jurkat cell line that lacks the classic cytoplasmic/nuclear Pg receptor. Pg inhibited the cell growth of both cell lines in a dose- and time-dependent manner to a similar extent, regardless of the status of caspase-8 expression. The activation of caspase-9 and -3 was observed in both cell lines following treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…This report concurs with others studies suggesting that apoptosis inhibition produced by P in teleost granulosa cells and Jurkat cells are also mediated through mPRα [50,51].…”
Section: Discussionsupporting
confidence: 93%
“…This report concurs with others studies suggesting that apoptosis inhibition produced by P in teleost granulosa cells and Jurkat cells are also mediated through mPRα [50,51].…”
Section: Discussionsupporting
confidence: 93%
“…It had also been proposed that the effect of progesterone on T cells is mediated via a membrane-bound PR, 3,20,21 the GR, 13 Glucocorticoid-induced T-cell death has been shown in a number of scenarios, first and foremost in the context of positive and negative thymocyte selection. 23,24 Our results extend these observations and confirm that progesterone induces T-cell death via the GR.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19] However, recent findings suggest that the conventional nuclear progesterone receptor (PR) might not be expressed or might be expressed at a very low level in T cells. It has also been suggested that progesterone could modulate T-cell function via binding to a membrane-bound PR expressed in T cells 3,20,21 or exerts its effects on T cells via binding to the glucocorticoid receptor (GR). It has also been suggested that progesterone could modulate T-cell function via binding to a membrane-bound PR expressed in T cells 3,20,21 or exerts its effects on T cells via binding to the glucocorticoid receptor (GR).…”
Section: T Reg Cells Can Inhibit Effector T (T Eff )mentioning
confidence: 99%
See 1 more Smart Citation
“…After treatment with the IC 50 value of PDTC at 0.3 µM for 24 h, cell cycle analysis was performed using a FACSCanto flow cytometer (Becton-Dickinson, CA, USA) according to methods reported previously with modifications (24,25). A total of 10,000 events were acquired and Diva software and ModFit LT™ Ver.3.0 (Verity Software House, ME, USA) were used to calculate the number of cells at each sub-G 1 , G 0 /G 1 , S and G 2 /M phase fraction.…”
Section: Cell Cycle Analysismentioning
confidence: 99%